Chapter The monastic heritage in the Saronic gulf (Greece). Architectural and environmental surveys of the architecture and coastline - Burda, Andronira (Proceedings e report, 2020)
The research itinerary is aimed at getting to know the monastic complexes in the Saronic Gulf (Greece) with operations of an investigative nature, to which are added references on religious and environmental themes which, in relation to architecture, expose the compositional and structural beauty of the Greek coastline. The study presents the survey of some Monasteries in the Saronic Gulf in southern Greece, such as the Monastery of the Spring Fountain on the island of Poros, the Monastery of the Assumption of the Virgin Mary on the island of Hydra and the Monastery of St. Nicholas in Spetses.